The role of lipase maturation factor 1 in hypertriglyceridaemia and atherosclerosis: An update - Siarhei A Dabravolski; Alexey V Churov; Vasily N Sukhorukov; Tatiana I Kovyanova; Dmitry F Beloyartsev; Irina N Lyapina; Alexander N Orekhov (SAGE Open Medicine)
Lipase maturation factor 1 is an endoplasmic reticulum-resident transmembrane protein, which acts as a critical chaperone necessary for the folding, dimerisation, and secretion of lipases. In this review, we summarise data about the recently revealed role of lipase maturation factor 1 in endoplasmic reticulum redox homeostasis, its novel interaction partners among oxidoreductases and lectin chaperones, and the identification of fibronectin and the low-density lipoprotein receptor as novel non-lipase client proteins of lipase maturation factor 1. Additionally, the role of lipase maturation factor 1-derived circular RNA in atherosclerosis progression via the miR-125a-3p/vascular endothelial growth factor A\Fibroblast Growth Factor 1 axis is discussed. Finally, we focus on the causative role of lipase maturation factor 1 variants in the development of hypertriglyceridaemia – a type of dyslipidaemia that significantly contributes to the development of atherosclerosis and other cardiovascular diseases via different mechanisms.